Estrogenicity of novel phase I and phase II metabolites of zearalenone and cis-zearalenone. (October 2015) - Drzymala, Sarah S.; Binder, Jennifer; Brodehl, Antje; Penkert, Martin; Rosowski, Mark; Garbe, Leif-Alexander; Koch, Matthias
Abstract: Zearalenone and its cis -isomer, cis -zearalenone, are nonsteroidal mycotoxins that elicit an estrogenic response upon binding to the estrogen receptor. This study compares the estrogenicity of eleven congeners including novel metabolites as 15-OH-zearalenone, zearalenone-14-sulfate, α- cis -zearalenol and β- cis -zearalenol using the E-Screen assay. Overall, a change in the configuration from trans to cis retains significant estrogenic activity. In contrast, alterations of the aromatic moiety including hydroxylation and sulfation showed a markedly decreased estrogenicity when compared to zearalenone. Graphical abstract: Highlights: First assessment of estrogenicity of α- and β-cis-ZEL, 15-OH-ZEN, and ZEN-14-sulfate. α-cis-ZEL shows even elevated estrogenicity compared to its parent compound cis-ZEN. Modifications on the aromatic moiety generally decrease estrogenic activity. Change from trans to cis configuration does not have a major impact on estrogenicity.